ANALISIS HUBUNGAN FAKTOR-FAKTOR EKSTERNAL DENGAN MOTIVASI KERJA PENYADAP KARET PADA KEBUN NGOBO PTPN IX (PERSERO) DI KABUPATEN SEMARANG - Vini Arumsari (Jurnal Dinamika Sosial Ekonomi, 2007)
The aim of this research was to analyze the relationship between the external factors and work motivation of the tapper of rubber. This reseach that was the case study in Kebun Ngobo (Afdeling Setro and Afdeling Jatirunggo) PTPN IX (Persero) at Semarang Regency which the research locations were decided purposively. Then, the primary data were collected from 75 respondents of the tapper of rubber using the simple random sampling which 40 respondents at Afdeling Seton and 35 respondents at Afdeling Jatirunggo together. The Rank Spearman correlation was used in the data analysis. The result showed that the wages and the leadership styles of foreman (leadership styles of human and producion) were significant relationship to the work motivation of the tapper of rubber at Afdeling Setro as well as Afdeling Jatirunggo.Key Words : Tapper of Rubbel; Exterrzatl Factors, Work Motivation